Combining Complete Blood Count with Differential Count; C-Reactive Protein and Band Neutrophils in Diagnosis of Early onset Neonatal Sepsis - Khawaja Abrar Ahmed, Manzoor Ali Khan, Syed Zakir Naqvi, Ishtiaq Ahmed Mughal, Mohsna Saeed Zia, Arzoo Idrees, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the diagnostic accuracy of complete blood count with band versus total neutrophil ratio and C-reactive proteins as an efficient analytical procedure for determining early onset sepsis in neonates. Study design: Cross sectional analytical study Place and duration of study: Department of Paediatric Medicine, Abbas Institute of Medical Sciences Muzafarabad, AJ Kashmir from 01-02-2022 to 31-07-2022. Methodology: Fifty patients were enrolled. Coulter counter was used for analyzing leucocytes of the neonates. Thin film-smears were generated by the laboratory scientist for identifying band neutrophils separately from mature neutrophils. C-reactive proteins level <5mg/dl was considered as negative. Thio-glycate-oxide in liquid form was used for 2ml neonatal blood culture analysis mixed in the 20ml medium at 36 degree celsius. Results: There were 28 (56%) males and 22 (44%) females. The mean age of the neonates was 1.6± 0.77 days. The mean weight of the neonates was 2.4±0.51kg with a range of 4-1.2kg. A variance of band versus total neutrophil ratio was significantly higher in cultures which were positive than negative such as 70% vs 25%. There was also significant percentage of C-reactive proteins positive in positive sepsis cultures in comparison to negative blood culture. Conclusion: A combination of complete blood count with differential count, white blood cell analysis with band versus total neutrophil ratio and c-reactive proteins is an efficient early analytical procedure for determining early onset sepsis in neonates as gold standard test blood culture is time taking. Key Words: Complete blood count, C-reactive protein, Total neutrophils ratio, Early onset neonatal sepsis.